1981
DOI: 10.1039/f19817700177
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of saturated hydrocarbons with rhenium powder catalyst

Abstract: HydrogenAeuterium exchange in methane, ethane and propane, hydrogenolysis of ethane, n-butane and isobutane and chemisorption of methane and ethane have been studied on rhenium powder catalysts.The kinetic isotope effect and the rate sequences of the exchange reactions mentioned above show that the rate limiting step is C-H bond dissociation.Ethane hydrogenolysis overlaps ethane exchange at 523 K. The hydrogenolysis reaction order with respect to hydrogen is slightly positive for ethane and greater than unity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One method of accomplishing greater selectivity to aromatics is by the addition of modifiers to the catalyst and the inclusion of sulfur to the feed stream. Examples that have proved industrially successful are the addition of lead, tin or germanium to the traditional monometallic (Pt/Al 2 O 3 ) or bimetallic (Pt–Re/Al 2 O 3 or Pt–Ir/Al 2 O 3 ) reforming catalysts 3–7. It has been reported that the superior activity and the enhanced selectivity of the supported bimetallic Pt–Re catalyst could not have been possible without the presence of impurities such as sulfur in the feed stream; deliberate addition of this impurity into the feed has become the usual practice in the reforming industry 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…One method of accomplishing greater selectivity to aromatics is by the addition of modifiers to the catalyst and the inclusion of sulfur to the feed stream. Examples that have proved industrially successful are the addition of lead, tin or germanium to the traditional monometallic (Pt/Al 2 O 3 ) or bimetallic (Pt–Re/Al 2 O 3 or Pt–Ir/Al 2 O 3 ) reforming catalysts 3–7. It has been reported that the superior activity and the enhanced selectivity of the supported bimetallic Pt–Re catalyst could not have been possible without the presence of impurities such as sulfur in the feed stream; deliberate addition of this impurity into the feed has become the usual practice in the reforming industry 8–11.…”
Section: Introductionmentioning
confidence: 99%